PENGARUH SMART CITY DALAM MENENTUKAN KEBERHASILAN CITY BRANDING PADA KELOMPOK TARGET PENDUDUK DI KOTA SURABAYA - Shinta Permana Putri (Prodi Magister Teknik Sipil Unsyiah, 2023)
City branding has been widely applied in cities in Indonesia, including the city of Surabaya. However, the branding efforts implemented are still not running properly. In the case of Surabaya City, there is still a separation between Surabaya's physical identity and the identity associated with the citizens. Thus this research was conducted with the aim to identify the city's identity as associated by the citizens of Surabaya. The research method used is a quantitative method with analytical techniques namely descriptive statistics. The results of this study indicate that the current image of the city of Surabaya associated with its citizens is a smart city. The implementation of smart city innovations has an effect on increasing the positive image of Surabaya. This positive image then influences satisfaction and increase their long-term commitment to stay. Even so, government intervention is still needed to improve smart mobility services and increase citizen participation in utilizing smart city services. These findings indicate that currently the Surabaya's city image has changed in a positive direction towards its technological innovations. The results of this study contribute in enriching knowledge related to the influence of smart cities in the formation of Surabaya's city image.